The follow-up study the therapeutic effect of some hormonal disorders associated with the of the polycystic ovary syndrome in women in the city of Tikrit - May Nafi Yousif; Muneif Saab Ahmed; Mossa M. Marbut (Journal of Madenat Alelem University College, 2017)
The study was designed the therapeutic effect on some disorders hormonal random sample of 96 women of married patients polycystic ovary syndrome (PCOS) the ages between of 35-16 years who suffer from subfertility and infertility, acne and hair junk and increased body weight and ovulation disorder. Is one of the main symptoms of the disease, the occurrence of imbalance in the hormonal imbalance led to the events of PCOS in women, especially in the reproductive age, as was the follow-up examinations each patient before treatment and after 6 months of taking by each treatment ((3 months, compared to the results after all we have obtained ((3 months of treatment the results of examinations of patients in the pre-treatment through a treatment plan based on a modified pattern of diseased food life through a healthy diet and give treatment of oral contraceptive and fertility drugs And the use of sugar reducers such as (Glucophage or Metformine), the results of the statistical analysis of the study showed that hormone follicle stimulating hormone ( FSH) Testosterone, luteinizing hormone(LH) ,and Prolactin (PRL) showed a decline morally after 3 months of taking the treatment and continued decline of moral hormones themselves after 6) months to continue taking medication, compared with pre-treatment, while the hormone progesterone showed up significantly after 3 months and 6 months of the continuation of the patients in the take them treatment compared with pre-treatment, the positive results we have obtained after continuous treatment for a long time without a break had an impact in improving ovulation and recording cases of pregnancy for the first time among the samples studied .